Thermophysical Properties of Cryoprotectants. VIII. Dielectric Permeability of Some Cryoprotectants, Their Aqueous Solutions and Mixtures - Todrin, Aleksandr F.; Timofeyeva, Elena V. (Problems of Cryobiology and Cryomedicine, 2015)
There were summarised the reported data on static dielectric permeability for water, pure cryoprotectants, their aqueous solutions and mixtures. The empirical polynomial equations to calculate static dielectric permeability for water and pure cryoprotectants depending on temperature were derived. The empirical polynomial equations for aqueous solutions and mixtures of some cryoprotectants depending on either the temperature at fixed concentrations or the concentration at fixed temperatures were obtained. Probl Cryobiol Cryomed 2015; 25(2): 131-150.